Root acidification, a rapid method of screening soybean genotypes for low-phosphorus stress - Vengavasi, Krishnapriya; Pandey, Renu (The Indian Journal of Genetics and Plant Breeding, 2016)
Carboxylate efflux in response to low-phosphorus (P) is one of the plant’s adaptive strategies. Genotypic variation between the type and amount of root-exuded carboxylates determines the differential P acquisition efficiency (PAE) in soybean (Glycine max (L.) Merrill.). We compared direct (using HPLC) and indirect methods (total carbon exudation, and use of bromocresol purple dye) for quantifying root acidification. Total carbon exudation did not correlate to carboxylate efflux, whereas a significant linear relationship between exudate pH and carboxylate concentration suggested that measure of root acidification might predict the genotypic potential for low-P induced carboxylate efflux.